Pengembangan Manfaat Media Pembelajaran 3 Dimensi pada Bangun Ruang Bagi Guru Sekolah Dasar - Nurhasanah, Aprilia; Nasir, Muhammad; Santika, Vioni Wina; Dhea DTM, Baiq Wira; Ridho, Saufi; Latip, Abdul (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
Learning media is very important to develop in the world of education. However, there are still many teachers who have not developed media innovatively and in accordance with learning materials. The use of 3D media needs to be increased because students can actually practice mathematics learning spatial material. This community service is aimed at improving teachers' skills in creating learning methods so that they can provide more interactive learning for students. The service method is carried out using PAR (Participatory Action Research) or carried out in a participatory manner with residents at SDN 01 Sei Tatas Hilir school in the use of 3D space-building media. The results of this service activity were (1) getting a positive response from the school, (2) the teacher felt helped by the presence of 3D learning media in the building, (3) students participated in the learning enthusiastically and actively responded when the teacher provided the material.